The mechanism of rockburst induced by coal rock structure transient - Yongping WU; Shenghu LUO; Zhuangzhuang YAN; Panshi XIE; Chengyang TIAN; Tong WANG; Xicai GAO; Hongwei WANG; Ding LANG (Meitan xuebao)
Rock burst is one of the main disasters in deep coal mining. Revealing the mechanism of rock burst is the premise and foundation of its disaster evaluation, prediction and prevention. In this paper, theoretical analysis, numerical calculation, simulation experiment and engineering field test mutual feedback research methods are comprehensively used. Based on comprehensively determining the internal relationship between the spatial structure of overlying strata and its mechanical response, the mechanical response of coal and rock and the mechanism of rock burst under structural transient excitation are systematically studied. The results show that the mechanical properties and mechanical environment of the spatial structure of overlying strata are the internal and external causes of different mechanical responses of coal and rock in the mining area. The instantaneous instability of subsystems such as hard rock breaking, which will lead to the transient of the large system of the overlying rock space structure, and then cause the occurrence of the dynamic mechanical response (mine earthquake) and the step change of the static mechanical response of the coal rock mass in the stope. After the transient of the structure, in addition to the strain energy at the source, the mechanical response of the stress field, displacement field, strain energy field and gravitational potential energy field of the coal and rock in a larger range will also be transient. The instantaneous subsidence of overlying strata above the structural transient region, the sudden reduction of stress, and the release characteristics of strain energy and gravitational potential energy are obvious. The coal rock mass in the deep area outside the structural transient region sinks slightly, the stress increases suddenly, the strain energy aggregation characteristics are obvious, and the gravitational potential energy is slightly released. The total potential energy of coal rock mass in the stope decreases instantaneously, in which the strain energy of coal rock mass increases instantaneously, while the gravitational potential energy decreases instantaneously. At the same time, due to the influence of unloading, rebound and subsidence caused by the fracture of hard rock strata, When the mine earthquake occurs, not all the coal and rock mass in the area will be instantaneously loaded, and the coal mass near the structural transient area will be instantaneously unloaded. The instantaneous fracture of the hard rock stratum behind the working face will make the strike abutment pressure ‘Move forward instantaneously’, resulting in the stress state of ‘high static load + negative dynamic load’ in the high static load area of the coal body in front of the working face, while the stress state of ‘high static load + positive dynamic load’ appears in the high static load area of the coal body in the mining roadway, resulting in a phenomenon that the probability of rock burst in the mining roadway is much larger than that in the working face. In practical engineering, targeted prevention and control measures should be established based on the internal relevance between coal rock structure and its dynamic and static response, as well as the concept of “adjusting structure and controlling response”.